Mathematical Modeling and Simulation to Control the Spread of Multidrug-Resistant Tuberculosis - Sulasri Suddin; Elinora Naikteas Bano ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2021)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis that fails treatment will develop into multidrug-resistant tuberculosis. Research on the TB epidemic continues, particularly in the field of applied mathematics with modeling. In this study, we analyzed a suitable strategy in controlling the development of susceptible individuals to active tuberculosis and even multidrug-resistant tuberculosis. In this work, local stability analysis was carried out around the equilibrium point. Also, to see the most influential parameters in the epidemic, a sensitivity analysis was performed on basic reproductive factors. Besides, the final work was to do numerical simulations with some cases, so that the model could describe the disease's phenomena and characteristics.